2020
DOI: 10.33225/jbse/20.19.276
|View full text |Cite
|
Sign up to set email alerts
|

Explicit Teaching of Scientific Argumentation as an Approach in Developing Argumentation Skills, Science Process Skills and Biology Understanding

Abstract: Science educational standards are increasingly emphasising on argumentation skills. However, students' argumentation skills are often not developed well as their experience of science knowledge in schools is often in the form of uncontested facts. This research asserts that argumentation skills should be developed through explicit teaching of argumentation while engaged in practical work that draws on students' science process skills. In turn, developing argumentation skills also improves their science process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 38 publications
4
24
0
3
Order By: Relevance
“…The result suggests that students' improved understanding of the concepts of Antimicrobial Resistance was facilitated by the MADI-based activities, which highlighted the integration of scientific argumentation and inquiry-based learning within a metacognitive environment. These findings of the present study were consistent with the previous research (Celep, 2015;Celik & Kilic, 2014;Ping et al, 2020;Myers, 2015), which supported the effectiveness of ADI in improving students' understanding. To substantiate the quantitative findings, the thematic analysis of the focus group discussion is presented in Table 5.…”
Section: Change In Students' Conceptual Understandingsupporting
confidence: 93%
See 3 more Smart Citations
“…The result suggests that students' improved understanding of the concepts of Antimicrobial Resistance was facilitated by the MADI-based activities, which highlighted the integration of scientific argumentation and inquiry-based learning within a metacognitive environment. These findings of the present study were consistent with the previous research (Celep, 2015;Celik & Kilic, 2014;Ping et al, 2020;Myers, 2015), which supported the effectiveness of ADI in improving students' understanding. To substantiate the quantitative findings, the thematic analysis of the focus group discussion is presented in Table 5.…”
Section: Change In Students' Conceptual Understandingsupporting
confidence: 93%
“…Although the study did only focus on students' generation of scientific arguments consisting of claim, evidence, and reasoning, the results of the present study corroborate the findings of a great deal of the previous works that have examined the effect of ADI on students' argumentation skills (Cȩtin & Eymur, 2017;Fadillah & Deta, 2020;Kadayifci & Celik, 2016;Myers, 2015;Ping et al, 2020). These studies noted that students' argumentation skills could be developed when they are exposed to a teaching and learning environment infused with scientific argumentation.…”
Section: Change In Students' Argumentation Skillssupporting
confidence: 87%
See 2 more Smart Citations
“…Scientific reasoning and argumentation had a positive effect on students' achievement (Dofner et al, 2018) and this approach could be used to improve students' scientific knowledge. Ping, Halim and Osman (2020) found that students were able to provide explanations when using the argument, which included evidence supporting their opinion.…”
Section: Argumentation In Sciencementioning
confidence: 93%